Дослідження впливу управлінських помилок та недоліків на наближення будівельної компанії до банкрутства - Андрущенко, В. А. (Ways to Improve Construction Efficiency, 2013)
The article focuses on the essence of the concept of "A-Account" and its role in predicting bankruptcy, the analysis of practical approaches to the definition of administrative errors in enterprises of the construction industry have been done and the influence of each defect on the deterioration of vitality company have been defined.